How does mode of delivery associate with double burden of malnutrition among mother-child dyads?: a trend analysis using Bangladesh demographic health surveys - Tasmiah Sad Sutopa; Wasimul Bari (BMC, 2022)
Abstract Background The simultaneity of undernourishment among child and overweight/obesity among mothers in lower-and-middle-income-countries (LMICs) introduces a new nutrition dilemma, known as double burden of malnutrition (DBM). Amidst of such paradox, the hike of caesarean section (CS) delivery is also triggering child undernutrition and maternal obesity. A gap of knowledge regarding the effect of mode of delivery on DBM still persists. The study aims to explore the association between DBM at household level and mode of delivery over time in LMICs. Method The study used data from recent four consecutive waves of Bangladesh Demographic and Health Survey (BDHS) ranging from BDHS 2007 to BDHS 2017. It considered the mother-child pairs from data where mothers were non-pregnant women aged 15-49 years having children born in last 3 years preceding the survey. Bivariate analysis and Logistic Regression were performed to explore the unadjusted and adjusted effect of covariates on DBM. An interaction term of mode of delivery and survey year was considered in regression model. Results The study evinces a sharp increase of DBM rate in Bangladesh from 2007 to 2017 (2.4% vs. 6.4%). The prevalence of DBM in household level among the children delivered by CS is more than two times of those born by normal delivery (8.2% vs. 3.5%). The multivariate analysis also indicates that the children born by CS delivery are more likely to be affected by DBM at household level significantly than those born by normal delivery in each waves. Moreover, the odds ratio (OR) of DBM at household is increased by 43% for one unit change in time for normal delivery whereas CS delivery births have 12% higher odds of DBM at household level with one unit change in time. Conclusion The study discloses a drastic increase of rate of DBM among mother-child pairs over the time. It stipulates inflated risk of DBM at household with time for both mode of delivery but the children with CS delivery are at more risk to the vulnerability of DBM at household level. The study recommends a provision of special care to the mothers with CS delivery to reduce DBM at household.